2022
DOI: 10.1002/aepp.13267
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for sustainability and supply chain worker conditions: Evidence during COVID‐19

Abstract: Given coronavirus 2019 (COVID‐19), we empirically investigate whether consumers are willing to pay for greater sustainability and safer working conditions in food supply chains. We elicit consumer valuation via two consumer choice survey experiments and revealed preferences using mixed Logit discrete choice models. We find that consumers have a significant positive average valuation towards sustainability, but may require an average compensation to choose products produced under safer working conditions. Polic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…Consumers were WTP about $0.34/lb for moderate worker safety and $1.91/lb for enhanced worker safety. But the increase between moderate and enhanced worker safety supports the conclusion that consumers were differentiating between levels of the attribute in their decisions, results that are consisted with the findings of Campbell et al (2022).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Consumers were WTP about $0.34/lb for moderate worker safety and $1.91/lb for enhanced worker safety. But the increase between moderate and enhanced worker safety supports the conclusion that consumers were differentiating between levels of the attribute in their decisions, results that are consisted with the findings of Campbell et al (2022).…”
Section: Resultssupporting
confidence: 82%
“…Despite ample evidence of worker impacts, more direct examinations of WTP for worker safety in meat processing are scant. Another research paper by Campbell et al (2022) measured consumers WTP for sustainability and worker safety conditions in food supply chain to US consumers during the COVID pandemic. Overall, results of the experiment found that consumers are willing to pay premium values for food options that are environmentally sustainable and improve worker safety conditions during COVID.…”
Section: Literature Reviewmentioning
confidence: 99%